Top-Down, Routinized Reform in Low-Income, Rural Schools - Robert Bickel; Terry Tomasek; Teresa Hardman Eagle (Arizona State University, 2000)
Since 1991, the National Science Foundation has funded fifty-nine state, urban, and rural systemic initiatives. The purpose of the initiatives is to promote achievement in math, science, and technology among all students, and to encourage schools and communities to secure the resources needed to maintain such outcomes. The Appalachian Rural Systemic Initiative (ARSI) is a six-state consortium which focuses these efforts on low-income, rural schools. The primary means of accomplishing ARSI's aims is a one-day-one-school site visit, called a Program Improvement Review, done by an ARSI math or science expert. The centrally important Program Improvement Reviews, however, seem to be premised on unsubstantiated assumptions as to the static, easy-to-understand, easy-to-evaluate nature of educational achievement in rural Appalachian schools. As a result, the Reviews resemble exercises in early-twentieth century scientific management, and are unlikely to enhance achievement in science or math. Consequently, even if there is merit to the commonsense human capital approach to economic growth and development on which systemic initiatives are tacitly premised, this first- person account makes a case that desired payoffs are unlikely to follow from the work of ARSI.